Solving it: (a + b)³
1. Cube the first term. = a³.
2. Square the first term, then combine it with 3 and the last term. = 3a²b
3. Same procedure, but this time, square the last term instead of first term. = 3ab²
4. Cube the last term. = b³
FINAL = a³ + 3a²b + 3ab² + b³

To find the cube of binomial of the form (x+y)³
1.) find the cube of the first term
2.)the second term is three times the product of the square of the first and second term
3.)the third term is three times the product of the first term and the square of the second term
4.)the fourth term is the cube of the second term.
in symbols:
(x+y)³= x³+ 3x²y+3xy²+ y³